2021
DOI: 10.1111/cdev.13551
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation to Social and Nonsocial Dynamic Cues in Preschool‐Age Children

Abstract: The ability to learn from expectations is foundational to social and nonsocial learning in children. However, we know little about the brain basis of reward expectation in development. Here, 3-to 4-year-olds (N = 26) were shown a passive associative learning paradigm with dynamic stimuli. Anticipation for reward-related stimuli was measured via the stimulus preceding negativity (SPN). To our knowledge, this is the first study to measure an SPN in children younger than age 6. Our findings reveal distinct antici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 56 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…As we predicted, we found that repeated experience of another's valid gaze cueing elicited a larger SPN before the presentation of the animation, suggesting that infants started to anticipate the social reward after learning associations between the face, the validity of gaze cueing, and the events of shared attention. In line with a previous study showing that social cues elicited the SPN at preschool age (Engle et al, 2021), the gaze cues predictive to the social reward of shared attention elicited a larger SPN than invalid gaze cues. This finding suggests that infants around seven months old could learn associations between faces and events of shared attention, and these experiences evoke the social reward anticipations.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…As we predicted, we found that repeated experience of another's valid gaze cueing elicited a larger SPN before the presentation of the animation, suggesting that infants started to anticipate the social reward after learning associations between the face, the validity of gaze cueing, and the events of shared attention. In line with a previous study showing that social cues elicited the SPN at preschool age (Engle et al, 2021), the gaze cues predictive to the social reward of shared attention elicited a larger SPN than invalid gaze cues. This finding suggests that infants around seven months old could learn associations between faces and events of shared attention, and these experiences evoke the social reward anticipations.…”
Section: Discussionsupporting
confidence: 91%
“…The SPN has been found in three-to four-year-old children within 200 ms prior to the onset of the target and the amplitude was larger for social than non-social stimuli (Engle et al, 2021). To our knowledge, the youngest age in which the SPN can be observed was this age group around three-years-old, however, some physiological studies have shown that infants less than 1year-old can anticipate social rewards.…”
Section: Previous Studies Have Shown How Perceptual Information Of Ga...mentioning
confidence: 73%
See 3 more Smart Citations